Alterations of leptin in the course of inflammation and severe sepsis - Behnes, Michael; Brückmann, Martina; Lang, Siegfried; Saur, Joachim; Borggrefe, Martin; Hoffmann, Ursula (BMC infectious diseases, 2012)
The adipokine leptin regulates energy expenditure, vascular function, bone and cartilage growth as well as the immune system and systemic inflammatory response. Several activating effects towards T cells, monocytes, endothelium cells and cytokine production have been reported suggesting a protective role of leptin in the setting of an acute systemic inflammation. However, the pathophysiological role of leptin during severe sepsis is currently not elucidated in detail. This study aims to investigate leptin expression in cultured human adipocytes within an inflammatory model and in patients suffering from severe sepsis and evaluates treatment effects of drotrecogin alpha (activated) (DAA), the recombinant form of human activated protein C.